AGAMA DAN KEBUDAYAAN: POLEMIK RITUAL MA’PAKANDE TOMATE SUKU TORAJA MENURUT IMAN KRISTEN - Windi Sampa (Adisam Publisher, 2025)
This study examines the persistent practice of the Ma'pakande Tomate (or manta'da) ritual among the Christian community in Tana Toraja, despite their adherence to Christian teachings. This ritual, performed to honor long-deceased ancestors, is rooted in the belief that the spirits of ancestors who have